Evaluation of Antioxidant Activity of Some Selected Tropical Fruits in South Kalimantan, Indonesia - Efrilia Tanjung; Muhammad Hafidz MS; Iskandar Thalib; Eko Suhartono (Journal of Tropical Life Science, 2014)
In the present study antioxidant and antioxidant activity of some tropical fruits was evaluated. Antioxidants are compounds or molecules that can scavenging and prevent free radicals and reactive oxygen species that can caused a cell damage. Fruit was known as a source of antioxidant. South Kalimantan Indonesia, has a variety of fruit such as mentega, nangka, timun suri and kuranji. Study for evaluating the antioxidant levels and activity of those fruit were never been investigated. Thus, our study aim to measure the antioxidant levels and antioxidant activtity of those selected fruits. Ascorbic acid, lycopene, b-carotene levels and antioxidant activtity of four selected tropical fruits was evaluated using spectrophotometer. The result of this studied suggest that the four selected tropical fruits is potential antioxidant because it contained ascorbic acid, b-carotene, lycopene and had effect of scavenging radical hydroxyl, hydrogen peroxide and chellating ferrous iron.